Estilos de aprendizaje en alumnos del primer grado del ciclo avanzado en una institución de educación básica alternativa Callao - Solorzano Prado, Kimberlin Criz (2012)
The purpose of the next investigation was to know the styles of learning in the students in the first grade of high school in an educational Institution of Callao. The present study is simple descriptive with a sample not probabilistic of 90 students (34 are female and 56 are male). The instrument was applied is the questionnaire of Honey- Alonso (1994) adapted in Peru by Zavala (2008) that determines the preferences accord the style of learning of the students. So, it concluded that exists predominance in the theory style fallowed of the active, reflexive and pragmatic style.